The effect of financial technology on sustainability performance: Mediating role of green finance - Kusuma, Desta Rizky (Universitas Ahmad Dahlan, 2025)
Purpose-This study aims to determine the effect of the adoption of financial technology on sustainability performance through green finance as a mediating variable. In order to achieve sustainable performance in the banking industry, the adoption of financial technology as a support is necessary. In addition to adopting financial technology, the role of green finance is also considered important in supporting sustainable performance in the banking industry. Methodology-This study's sample consisted of 110 employees working at rural banks in Central Java, Indonesia. The questionnaires were physically distributed and filled out directly by employees. The data collected from the respondents was then tabulated and processed using Smart PLS. Findings-This study proves the partial influence of financial technology adoption on sustainability performance and green finance. Green finance has also been proven to have a positive effect on sustainability performance. In addition to its partial influence, green finance has also been proven to mediate the relationship between financial technology adoption and sustainability performance. Research Limitations-This study's limitations are the number of samples, which is still relatively minimal, and the scope of research objects, which is limited to a certain region. Therefore, the results of this study cannot be used as a basis for describing the answers of respondents and objects in other regions. Novelty-This research is expected to contribute to the banking industry so that companies can study and implement the adoption of financial technology and green finance. Implementing these two things has a positive impact on building or achieving a company's sustainability performance